Human immunodeficiency virus reverse transcriptase. A kinetic analysis of RNA-dependent and DNA-dependent DNA polymerization - Reardon, J E (The Journal of biological chemistry, 1993)
A minimal kinetic mechanism for HIV reverse transcriptase (RT)-catalyzed RNA-dependent and DNA-dependent DNA polymerization was determined by pre-steady-state kinetic methods to be: [formula: see text] where E, TP, dNTP, and PPi are RT, template-primer, 2'-deoxynucleoside 5'-triphosphate, and inorganic pyrophosphate, respectively. Defined sequence template-primers that encode for incorporation of dTTP were prepared by annealing either a 44-mer RNA template or a 44-mer DNA template (of the same sequence) to a 21-mer DNA primer (r44:d21-mer and d44:d21-mer, respectively). The values of the above kinetic constants were determined for dTMP and 3'-azido-3'-deoxythymidine 5'-monophosphate (AZTMP) incorporation into both template primers. The kcat and Km values calculated from these kinetic constants were similar to the values directly determined from steady-state experiments. Further, the net rate constants for processive incorporation of three successive nucleotides into the r44:d21-mer were similar indicating that a rate-determining step did not follow catalysis. A 20-fold difference in the rate constants (kp) for incorporation of dTMP into the r44:d21-mer versus the d44:d21-mer was largely responsible for the difference in the calculated processivity numbers of 340 and 5, respectively. Finally, the rate constant for pyrophosphorolysis of the 3'-AZTMP-terminated r44:d21-mer (kpyro) was similar to the rate constant for dissociation of the chain-terminated template primer from the enzyme (koff) indicating that millimolar concentrations of intracellular inorganic pyrophosphate would be required for pyrophosphorolysis of AZTMP-terminated retroviral genomes.